Labour Market Discrimination against Former Juvenile Delinquents: Evidence from a Field Experiment - Stijn Baert; Elsy Verhofstadt (Institute for the Study of Labor (IZA), 2013)
We identify hiring discrimination against former juvenile delinquents in a direct way. To this end we conduct a field experiment in the Belgian labour market. We find that labour market discrimination is indeed a major barrier in the transition to work for former juvenile delinquents. Labour market entrants disclosing a history of juvenile delinquency get about 22 percent less callback compared to their counterparts without a criminal record. This discrimination is more outspoken among the low-educated.
Keywords: C93; J2; J71; 330; hiring discrimination; field experiments; juvenile delinquency; transitions in youth